PENERAPAN PEMBELAJARAN AKTIF BERBASIS PROYEK DALAM MENGAJARKAN KONSEP STATISTIKA DI SEKOLAH DASAR - Tri Mulyani, Endang; Siti Lestari Dwi Wahyuningsih; Budi Murtiyasai; Nining Setyaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to explore the implementation of the Project-Based Learning (PjBL) model in teaching statistical concepts at the elementary school level to improve students' understanding and motivation. Using a descriptive qualitative approach and a case study method, this research involved sixth-grade students from SDN 03 Dayu Karangpandan, utilizing observation, interviews, and documentation as data collection techniques, analyzed thematically. The results show that PjBL successfully increased students' average scores from 65 to 85 and enhanced learning motivation through active engagement in surveys, data analysis, and project presentations. This method also promotes the development of 21st-century skills such as collaboration and critical thinking, despite challenges such as differences in student abilities and time constraints. In conclusion, PjBL is effective in improving the quality of statistical learning, provided that teacher guidance plays a crucial role in its success.